Development of Physics Test Instruments to Measure Problem Solving Skills on Dynamic Fluid Materials - Sanjaya, Aditya Putra; Tanjung, Yul Ifda; Mihardi, Satria (Universitas Negeri Padang, 2024)
Problem solving skills are a fundamental part of physics learning that must be possessed by students in facing challenges and problems that involve critical thinking, logical, systematic and able to make the right decisions. In fact, the availability of instruments to measure these skills is still limited. Based on that, the purpose of this research is to develop a test instrument based on problem solving skills based on Heller's stages on dynamic fluid material that meets the criteria for good instrument feasibility. This type of research is development research (Research and Development / R&D) with a 4D model consisting of 4 stages, namely define, design, develop and disseminate. The subjects of this study were XI grade high school students totaling 36 people for product testing. The results showed that the average value of content validity testing was 93.53% with very valid criteria, while the results of item validation in small and large groups showed that all ten test instruments were categorized as valid. In terms of reliability, the small group obtained a value of 0.84 which is classified as very high reliability and in the large group obtained a value of 0.78 which is classified as high reliability. The results of the student response test obtained a positive response in the small group of 81.00% with a good category and in the large group of 81.32% with a very good category. Based on the results of the study, it is concluded that the dynamic fluid material problem solving test instrument developed as many as 10 questions has met the eligibility criteria of the test instrument including validity and reliability so that it can then be used as a training medium and a measuring tool for problem solving skills.